Embedding of spatial equity in a rapidly urbanising area: Walkability and air pollution exposure. (December 2022) - Yu, Peiheng; Chen, Yiyun; Xu, Qinyi; Zhang, Shujin; Yung, Esther Hiu Kwan; Chan, Edwin Hon Wan
Abstract: This paper investigates the spatial relationship between walkability and air pollution exposure via a spatial vertical equity lens, and discusses the possible bias of healthy spaces with a special focus on age groups and housing prices. The urban centre of Wuhan, China, a rapidly urbanising area, is taken as the study area. The findings obtained are: (i) spatial inequities of the urban-rural gradient are evident in terms of walkability and air pollution exposure, and the combinations of the two measurements divide the study area into high walkability-low pollution exposure spaces ('sweet spot' locations), low walkability-high pollution exposure spaces ('sour spot' locations), high walkability-high pollution exposure spaces ('risky spot' locations) and low walkability-low pollution exposure spaces; (ii) both minors and seniors were inequitably treated in healthy space allocation, but minors are at a more significant disadvantage than seniors; and (iii) the communities with low housing prices exhibit low walkability and high air pollution exposure, suggesting that healthy spaces are more likely observed in economically advantaged communities. The study proposes a spatial lens to investigate the importance of embedding the notion of vertical equity in the built environment, and thus provides a conceptual framework to support sustainable urban planning and public health. Highlights: Spatial lens is adopted to investigate the equity embedded in the built environment. Measurements of walkability and air pollution exposure have both been improved. Minors, compared to seniors, are at a greater disadvantage in the built environment. Economically vulnerable groups are being squeezed out of healthy spaces. The research framework supports policies towards a more equitable environment.